2019
DOI: 10.1111/pbaf.12239
|View full text |Cite
|
Sign up to set email alerts
|

The Fiscal Impacts of Urban Sprawl: Evidence From U.S. County Areas

Abstract: This paper examines the fiscal impacts of urban development patterns in the United States. Previous studies have indicated that it is costly to provide public services in areas with low‐density, spatially expansive development, leading to higher per capita expenditures. However, theory would suggest alternate outcomes. This paper examines this question using a panel dataset of U.S. urban county areas and a specification allowing for potential nonlinearity between development patterns and per capita expenditure… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Depending on characteristics of the distribution network such as connection density (Shih et al, 2006; Youn Kim & Clark, 1988), additional service connections can achieve greater economies of scale, but only if the underlying relationships between volume of water provided, size of the distribution area, and density of service connections are not adversely changed (Torres & Morrison Paul, 2006). In general, research has shown that public service delivery in more densely populated urban areas is more cost‐effective compared to areas that are characterized by suburban sprawl (Goodman, 2019).…”
Section: Relevant Literaturementioning
confidence: 99%
“…Depending on characteristics of the distribution network such as connection density (Shih et al, 2006; Youn Kim & Clark, 1988), additional service connections can achieve greater economies of scale, but only if the underlying relationships between volume of water provided, size of the distribution area, and density of service connections are not adversely changed (Torres & Morrison Paul, 2006). In general, research has shown that public service delivery in more densely populated urban areas is more cost‐effective compared to areas that are characterized by suburban sprawl (Goodman, 2019).…”
Section: Relevant Literaturementioning
confidence: 99%
“…The pioneering study of the Real Estate Research Corporation (1974) estimated that the cost of providing schools, roads, and utilities under high-density can be 17-30% of the corresponding costs under low density. Since then, many other studies have been pointing to significant effects of urban sprawl on local finances in the US (Burchell & Mukherji, 2003;Carruthers & Ulfarsson, 2003Duncan & Frank, 1989;Frank, 1989;Goodman, 2019;Ladd, 1992).…”
Section: A Brief Review On Urban Sprawl and Local Public Financementioning
confidence: 99%
“…Other measures found in econometric estimations of the expenditure functions include the built-up area per capita (Hortas-Rico, 2014), indexes similar to the Lorenz curve (Nakamura & Tahira, 2008); degree to which residential areas are close to each other, the degree to which residential areas are close to the CBD, the degree to which residential units are close to each other within residential areas (Ida & Ono, 2019); and a sprawl index that represents the multidimensional form of urban sprawl (Gielen, Riutort-Mayol, Palencia-Jiménez, & Cantarino, 2018, 2019.…”
Section: A Brief Review On Urban Sprawl and Local Public Financementioning
confidence: 99%
“…Urban development and sprawling land-use patterns continue to pose significant challenges for the developed and developing world (Goodman, 2019;Inostroza et al, 2013;Musakwa and van Niekerk, 2014;Patacchini et al, 2009). Understanding the complex impacts of human settlement patterns on social and natural systems is critical for immediate and long-term policy decisions and ecosystem preservation (Ostrom, 2009a;Ramaswami et al, 2018).…”
Section: Introductionmentioning
confidence: 99%